2023
DOI: 10.3390/ijerph20021327
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Body Composition and Specific Motor Abilities According to Position in Elite Female Soccer Players

Abstract: Contemporary top-division soccer is characterized by high-intensity activity throughout the entire match, which also requires high levels of a wide range of the players’ functional and motor abilities. Furthermore, motor and functional requirements vary in relation to the players’ position on the pitch. In view of the above, the objective of this study was to determine any differences in body composition and specific motor abilities in relation to position. Twenty elite female soccer players (age: 20.90 ± 3.70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…Soccer is simultaneously a physical and cognitive activity that has proven itself irresistibly popular with people all over the world ( Stanković et al, 2023 ). Contemporary top-level soccer is marked by high-intensity activity throughout the entire match, also requiring a high level of a wider array of players’ functional and motor abilities ( Tierney et al, 2016 ; Leyhr et al, 2021 ; Hermassi et al, 2022 ; Hermassi et al, 2022 ; Silva et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soccer is simultaneously a physical and cognitive activity that has proven itself irresistibly popular with people all over the world ( Stanković et al, 2023 ). Contemporary top-level soccer is marked by high-intensity activity throughout the entire match, also requiring a high level of a wider array of players’ functional and motor abilities ( Tierney et al, 2016 ; Leyhr et al, 2021 ; Hermassi et al, 2022 ; Hermassi et al, 2022 ; Silva et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary top-level soccer is marked by high-intensity activity throughout the entire match, also requiring a high level of a wider array of players’ functional and motor abilities ( Tierney et al, 2016 ; Leyhr et al, 2021 ; Hermassi et al, 2022 ; Hermassi et al, 2022 ; Silva et al, 2022 ). Moreover, soccer is a multifaceted sport which comprises several activities (tackles, jumps, and direction, and speed changes) that tax numerous technical, cognitive, neuromuscular, and metabolic processes ( Leyhr et al, 2021 ; Hermassi et al, 2022 ; Stanković et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Michael et al [ 41 ] found a correlation between the T-test and fat percentage ( r = 0.61. p < 0.01) in U14 soccer players. In the same context, data collected by the study by Stanković et al [ 42 ] indicate that strikers who have a larger fat-free body mass ratio perform better on tests measuring their explosive strength and agility. However, there was a negative relationship between agility tests and BF% in elite female soccer players for midfield line players and defenders.…”
Section: Discussionmentioning
confidence: 99%
“…Strength and conditioning coaches place a strong focus towards developing a healthy body composition in soccer players. Increases in fat free mass can lead to superior musculoskeletal performance as a result of increased contractile units, while enhanced body composition can reduce cardiovascular strain whereby improving cardiorespiratory performance ( 10 ). Our hypothesis was confirmed with a meaningful decrease in body fat % of −3.7%, a change beyond that of the typical error of 2.5% ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of body composition on athletic performance measures in female soccer players has recently been demonstrated by Stankoiv et al, where increases in fat free mass exhibited significant, and positive associations to musculoskeletal function when measured using vertical jump performance, agility, as well as running speed. Additionally, decreases in body fat (%) were observed to be significantly associated to enhanced cardiorespiratory performance ( 10 ). As such, strength and conditioning coaches place large significance towards prescribing exercise programs that are either designed to maintain or improve muscle mass depending on the training cycle within the yearly program.…”
Section: Introductionmentioning
confidence: 99%